Photovoice: An Evaluation of the Students’ Participation in Stay at Home, Magtanom Outreach Program - Maria Aurora Caballero; Raul Burce (Journal of General Education and Humanities, 2025)
Conducted in the Philippines during the COVID-19 pandemic, this study employed Photovoice as a participatory platform for Civic Welfare Training Service (CWTS) students to express their experiences and evaluate their SAHMOP training in Partido State University at the foot of Mount Isarog and near coastal areas. Photovoice was also employed to collect and document students’ reflections on their experiences with home gardening, family participation, and civic engagement under the NSTP framework. It looked at and interpreted images to understand positive volunteer work, civic awareness, discipline, and proactive efforts. Among the 900 CWTS students trained under SAHMOP, 596 completed ten vegetable gardening stages. During the photovoice exhibit, students from marginalized communities expressed that the training fostered a sense of belonging and civic responsibility.  One student reflected, "We didn’t just do this for grades - we built friendships and learned to care for our community through gardening."  This participatory experience prepared students for real-world concerns, including climate change. Some underprivileged children showed the exhibit's inter-raters their best photovoice. Their response as policymakers was to create policies that promote SAHMOP in barangay local government units (LGUs) by linking them with Sustainable Development Goals (SDGs) on excellent education, sustainable cities and communities, and partnerships.